Spatio-Temporal Analysis Of Hydro-Meteorological Drought In The Muda River Basin, Malaysia - Luhaim, Zibeon (2022)
This study aims to analyse the spatiotemporal changes of historical droughts over the Muda River Basin (MRB) from 1985 to 2019 using the Standardized Precipitation Index (SPI) and Standardized Streamflow Index (SSI) at 1-, 3-, 6-, & 12-month time scales. The Mann-Kendall test and Sens’ slope were used to evaluate the trends and magnitude changes of the droughts, respectively. While, Spearman’s rho was applied to understand the relationships between droughts and large-scale atmospheric circulations such as the El-Nino Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), and the Madden-Julian Oscillation (MJO).